The eartquake effect of single storey RC building structure due to surrounding earthquake in Malaysia - Fatin Nadiah, Kamarudin (2016)
Nowadays, earthquake had happened in Malaysia. So, a study of earthquake was carrying out for Malaysia which is for single storey concrete building. For this study, there are two software being used to get data of effect of single storey building due to surrounding earthquake and not surrounding earthquake which are ESTEEM software and SAP 2000 software. ESTEEM software and SAP 2000 software have differences step to use it and advantage of using the software to the engineer or users. ESTEEM software and SAP 2000 software produce differences of result and this research is carry out to know why there are difference between this two software. This is to determine comparative analysis using ESTEEM software and SAP 2000 software. By using SAP 2000, the best mode, shape of three vibration analysis can be determined. ESTEEM software and SAP 2000 software can insert of earthquake data but there are still differences of this each software. SAP 2000 using Acheh's data of earthquake but for ESTEEM software insert for angle of earthquake or waves which will come to the building.